(untitled) (Altre Modernità, 2014)
Liliane Atlan, who was born in Montpellier in a Jewish family luckily escaped the deportations race, oppressed by a sense of guilt for having survived the genocide, is a form of redemption in writing by publishing poems and dramas, récits and radio plays in which he expressed the problems and the existence of Judaism, which for their artistic quality has given him awards and accolades literary and historical figures such as the Prix Memoire de la Shoah in 1999. Of particular importance as some of his plays Monsieur Fugue ou le mal de terre and La petite voiture et de voix de flammes that brought dramatic and spiritual facts related to the Jewish world and the contemporary